Determinants of Corporate Dividend Payout in Nepal - Adhikari, Nabaraj (NRB Economic Review, 2015)
There are several studies that investigated determinants of corporate dividend payout in developed and emerging stock markets. Such a study is scant in pre-emerging stock markets like that of Nepal. Therefore, the purpose of this paper is to investigate the determinants of corporate dividend payout in Nepal. This paper examines whether enterprises’ characteristics affect dividend payouts of the enterprises listed on Nepal Stock Exchange Ltd. A priori hypothesis between relationship of the dividends paid by the enterprises and enterprises’ characteristics- net profits, size, lagged dividends, liquidity, risk, investment opportunity set, and number of shareholders are set based on theoretical framework and other empirical studies, and tested on 22 listed enterprises covering a 5-year period, 2009 to 2013 by employing regression model. Purposive sampling technique is used to select the enterprises for the study. The relationships of variables firstly analysed for overall sector and further for sub-sectors of financial and non-financial sector. Overall sector analysis is performed through pooled cross-sectional data. Further to check sectoral differences, sector wise regression analysis is performed. The results, in overall, reveal that profitability, size, and liquidity are major determinants of corporate dividend payout in Nepal. This study also reveals that there is sector specific importance of the determinants of corporate dividend payout in Nepal.